Effects of Dietary Selenium Sources on Physiological Status of Laying Hens and Production of Selenium-Enriched Eggs - Qiu, Kai; Zheng, Jun-Jie; Obianwuna, Uchechukwu Edna; Wang, Jing; Zhang, Hai-Jun; Qi, Guang-Hai; Wu, Shu-Geng (Frontiers in Nutrition, 2021)
Developing new sources of organic selenium (Se) has potential benefits for animal production and human nutrition via animal-based foods enriched with Se. The objective of this study was to evaluate the effects of Se-enriched insect protein (SEIP) in comparison to other sources sodium selenite (SS) and selenium enriched yeast (SEY), on performance, egg quality, selenium concentration in eggs, serum biochemical indices, immune capacity, and intestinal morphology of laying hens. Four hundred and fifty 24-week-old Hy-Line Brown laying hens with 94.0 ± 1.5% laying rate were randomly allocated to 5 groups with 6 replicates of 15 hens each. The control diet was prepared without adding exogenous selenium (calculated basal Se content of 0.08 mg/kg). The normal group was fed basal diets supplemented with 0.3 mg/kg of Se provided by sodium selenite. Three treatment groups (SS, SEY, and SEIP, respectively) were fed basal diets supplemented with 2 mg/kg of Se provided by sodium selenite, Se-enriched yeast, and SEIP, respectively. The feeding trial lasted for 12 weeks. Results revealed that dietary supplementation of 2 mg/kg of Se increased egg weight, decreased feed conversion ratio, and enhanced the antioxidant capacity of eggs in laying hens relative to the control group while no significant differences were observed among SS, SEY, and SEIP treatment groups for same. The organic source of Se provided by SEY or SEIP showed higher bio-efficiency as indicated by higher selenium content in eggs of SEY and SEIP compared to SS, although higher content was observed in SEY compared to SEIP. Also, the organic Se source significantly improved antioxidant capacity and immune functions of laying hens than the inorganic Se source. Diets supplemented with SEIP and SS significantly improved jejunal morphology of the laying hens compared to SEY while SEIP was more effective than SEY to improve the oviduct health of laying hens. The results of the present study evidently points the additive effect and non-toxicity of SEIP. Thus, SEIP could be used as another organic source of Se in diet of laying hens and production of selenium-enriched eggs for humans.